Impacts of auditory-tactile training on auditory perceptual learning - Joyner, Chelsea N. (Kansas State University, 2023)
Perceptual experiences tend to be multisensory ones, yet multisensory perceptual learning is not as often studied as learning in the individual senses (i.e. vision, audition, or somatosensory). These studies looked at auditory-tactile training in comparison to unimodal auditory-only training on auditory perceptual tasks. A series of experiments were completed in which participants were trained with unimodal auditory-only or synchronous, multimodal auditory-tactile sounds in temporal discrimination, perceptual categorization, and perceptual thresholding tasks. Some experiments tested generalization to auditory-only detection tasks or used auditory-only testing of the same task used during multisensory training. Sensitivity (d’) and thresholds were measured and compared across training conditions, and over time. These experiments were expected to replicate multisensory learning enhancements in perceptual sensitivity, but extend this literature to the somatosensory domain and its relationship with audition. Overall, these studies found an increase in learning over time, so these experimental paradigms do work for training purposes. However, there was only one occasion in which auditory-tactile learning occurred at an accelerated rate over time compared to the auditory-only training, and we believe this occurred due to an initial disadvantage of auditory-tactile presentation on perception. We discuss the possible mechanisms of multisensory learning benefits, and why they may not have been found in these studies. This research will be used to establish a behavioral paradigm for future EEG research to study auditory evoked potentials (AEPs) and the plasticity associated with multisensory training effects. In the applied realm, this research may inform optimal perceptual training methods that are relevant to real-world perception issues (e.g., reactions to familiar sounded alarms; rehabilitation in auditory processing disorders).
Keywords: Perceptual learning; Plasticity; Crossmodal; Audiotactile; Training